Averaged equations for injection locked semiconductor lasers - Nizette, Michel; Erneux, Thomas; Gavrielides, Athanasios; Kovanis, Vassilios (Physica. D, 2002)
An averaging method valid for strongly nonlinear oscillators is used for the first time to describe the pulsating intensity regimes of semiconductor lasers subject to injection. Slow-time equations are derived which are valid for solutions of arbitrary amplitude. These averaged equations do not require the knowledge of a particular bifurcation point and are a good starting point for further analysis. Bifurcation points to periodic or quasiperiodic intensity oscillations are determined analytically by exploring certain limits of the parameters. Finally, we illustrate the strength and weakness of these expressions by comparing bifurcation diagrams obtained from the averaged equations and from the original laser equations.